Tuning Microparticle Porosity during Single Needle Electrospraying Synthesis via a Non-Solvent-Based Physicochemical Approach - Yuan Gao (Polymers, 2015)
Porous materials, especially microparticles (MP), are utilized in almost every field of engineering and science, ranging from healthcare materials (drug delivery to tissue engineering) to environmental engineering (biosensing to catalysis). Here, we utilize the single needle electrospraying technique (as opposed to complex systems currently in development) to prepare a variety of poly(ε-caprolactone) (PCL) MPs with diverse surface morphologies (variation in pore size from 220 nm to 1.35 µm) and architectural features (e.g., ellipsoidal, surface lamellar, Janus lotus seedpods and spherical). This is achieved by using an unconventional approach (exploiting physicochemical properties of a series of non-solvents as the collection media) via a single step. Sub-micron pores presented on MPs were visualized by electron microscopy (demonstrating a mean MP size range of 7–20 μm). The present approach enables modulation in morphology and size requirements for specific applications (e.g., pulmonary delivery, biological scaffolds, multi-stage drug delivery and biomaterial topography enhancement). Differences in static water contact angles were observed between smooth and porous MP-coated surfaces. This reflects the hydrophilic/hydrophobic properties of these materials.